Explaining Islamic insurgencies the case of al-Jamaah al-Islamiyyah and the radicalisation of the Poso .conflict, 2000-2007 - Karnavian, M. Tito (Imperial College Press insurgency and terrorism series, 2015)
Explaining Islamist Insurgencies explains how and why the process of Islamist radicalisation is an important step towards acts of terrorism and in the formation of terrorist organisations by focusing on Poso, a small town in Indonesia that experienced years of armed sectarian conflict between Muslim and Chrisitian communities in 2000-2007.